Perancangan Interior Pusat Informasi E-Sports di Surabaya - Fanjaya, Prathama Nugraha (Intra, 2015)
The design is made to introduce what is E-Sports to people who havenât know about E-Sports and the other purpose is to increase indonesian players skill on E-Sports. This design is not only for introduce the people about what is E-Sports but also allow them to be able to learn all about E-Sports, from general knowledge till try how to play E-Sports properly, until Indonesian E-Sports player are able to compete with others countries.This design uses the function space so that people can visit to get information clearly and a new place for an interesting exercise, by displaying a collection of objects and their descriptions, and supported by an attractive interior atmosphere.